Dunhuang- geneza powstania i strategiczne znaczenie miasta za czasów cesarza Wudi z dynastii Han - Morek, Daniel (Instytut Historyczny Uniwersytetu Wrocławskiego, 2022)
Dunhuang was arguably one of the most important cities on the so-called Silk Road. Its establishment was made possible due to Han emperor Wudi’s war against the nomadic tribes of the Xiongnu, who posed a major threat to the Chinese during the early years of the Han dynasty. The city was established as a strategic military settlement that was part of the regional tuntian system, and its role was to help secure the western borders of the empire. Due to the discovery of potential trading partners in the west during the reignof emperor Wudi, as well as the war which resulted in the vassalization of city states in the Takla Makan desert, Dunhuang became a trading hub from where caravans from the Chinese interior travelled west, which only increased its strategic value. This article will discuss what caused the evolution of Dunhaung from a frontier tuntian settlement into a major trading hub and strategically important city.
Keywords: Han Dynasty; Silk Road; Dunhuang; Hexi Corridor; Emperor Wu; Xiongnu; Sogdians; tuntian